2011
DOI: 10.1021/ac102431d
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Label-Free DNA Electrical Detection on Graphene Platform

Abstract: The anodized epitaxial graphene (EG) electrode demonstrates a high level of performance for electrochemical impedance as well as differential pulse voltammetry detection of immobilized DNA and free DNA, respectively, at solid-liquid interfaces. On the anodized EG surface, because of the presence of oxygen functionalities as well as π conjugated domains, the anchoring of the DNA probe can be achieved by either covalent grafting or noncovalent π-π stacking readily. The effect of different binding modes on the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 73 publications
6
106
0
3
Order By: Relevance
“…From the enzyme based sensor, the sensitivity of sensor with covalent attachment was improved compared to the one of non-covalently absorbed receptors. This was also in good agreement with the DNA recognition sensors [12]. In this case, an impedimetric sensor was built from anodized epitaxial graphene.…”
Section: Amidationsupporting
confidence: 80%
See 1 more Smart Citation
“…From the enzyme based sensor, the sensitivity of sensor with covalent attachment was improved compared to the one of non-covalently absorbed receptors. This was also in good agreement with the DNA recognition sensors [12]. In this case, an impedimetric sensor was built from anodized epitaxial graphene.…”
Section: Amidationsupporting
confidence: 80%
“…Independently of the approach, the functionalization procedure should be designed according to the sensors characteristics. The detection mechanism should be therefore taking into account so that the functionalization procedure enhances the sensitivity [12,20,43,48]. For such purpose, the functionalization requires suitable characterization tools that could give evidences of the effective immobilization of the receptor via quantitative and qualitative determination.…”
Section: Discussionmentioning
confidence: 99%
“…Due to rather poor electrocatalytic activity of intrinsic graphene and graphite [25][26][27], the electrodes were activated by anodization [28,29]. It has been shown that during electrochemical oxidation, several functional groups connect to the graphite basal plane and many multivacancies and small etch pits appear [30].…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have appeared in the literature on the potential in sensitive and selective detection of protein and DNA using various graphene platforms. [22][23][24][25][26] Graphene has also been shown to be superior to metallic surfaces in terms of bio-compatibility and chemicalstability. [ 27 , 28 ] Molecular charge transfer between molecules and graphene has been shown to be signifi cant for selected families of molecules.…”
mentioning
confidence: 99%